The first step was the combine the like terms; in this example he is subtracting the 3x on both sides of the =.
If you were to solve the equation it would look like this:
2x+6=3x-8
-3x -3x
-x+6=-8
-6 -6
-x=-14
/-1 /-1
x=14
Answer: Total cost would be $53. 24 including tax which is $3.25
Step-by-step explanation:
Answer:
Step-by-step explanation:
Answer:
y=x+10
Step-by-step explanation:
1.) y-1=1(x+9)
2.) y-1=x+9
3.) y=x+10
Answer:
x + y = 5
<u>3x - 4y = 8</u><u> </u><u> </u><u> </u>
3x + 3y = 15
<u>3x - 4y = 8 </u>-
7y = 7
y = 1
x + y = 5
x + 1 = 5
x = 4
x = 4
y = 1
Hope it helps!